The angiotensin receptor and neprilysin inhibitor, LCZ696, in heart failure: A meta-analysis of randomized controlled trials. Issue 41 (14th October 2022) - Chen, Yan; He, Qian; Mo, Dun-Chang; Chen, Long; Lu, Jia-Lu; Li, Rui-Xing; Huang, Jie
Abstract : Background: LCZ696 is a novel neuroendocrine inhibitor that has been widely used in heart failure (HF). However, its advantage over other neuroendocrine inhibitors, such as angiotensin-converting enzyme inhibitors (ACEis) and angiotensin-receptor blockers (ARBs) has not been fully elucidated. This study aimed to provide the latest evidence regarding the efficacy and safety of LCZ696 as compared to other ACEis and ARBs with regards to the treatment of HF. Methods: We systematically searched databases, including PubMed, Embase, and the Cochrane Library, for relevant randomized controlled trials (RCTs). The outcome measures included all-cause mortality, rate of hospitalizations for HF, rate of death from cardiovascular causes, change in N-terminal pro-brain natriuretic peptide (NT-proBNP) levels, and decline of renal function. Results: Five RCTs involving 19, 078 patients were identified. The meta-analysis indicated that LCZ696 was associated with a significant reduction in all-cause mortality (hazard ratio [HR] = 0.84; 95% confidence interval [CI], 0.76–0.93; P = .0005), rate of hospitalizations for HF (HR = 0.80; 95% CI, 0.73–0.87; P < .00001), reduction in NT-proBNP levels (rate ratio = 0.78; 95% CI, 0.70–0.88; P < .0001), and decline in renal function (odds ratio = 0.77; 95% CI, 0.68–0.88; P < .0001) compared with ACEis and ARBs. However, there was no statistical difference in the rate of death from cardiovascular causes (HR = 0.86; 95% CI, 0.72–1.03; P = .09) between LCZ696 and ACEis and ARBs. Conclusion: LCZ696 is superior to ACEis and ARBs in the treatment of HF. Hence, it should be more widely used clinically.